Step-by-step explanation:
hopefully it makes sense and is visible
:)
Answer:
It's table D
Step-by-step explanation:
I just took the test.
X^2-2x -3 =0
a =1 b =-2 and c = -3
x = - (-2) +/- sqrt (-2)^2 - 4(1)(-3)
--------------------------------------
2(1)
x = + 2 +/- sqrt [(4) - 4(-3)]
-------------------------------
2
x = +2 +/- sqrt [4 + 12]
--------------------------
2
x = +2 +/- sqrt[16]
-------------------
2
x = +2 +/- (4)
-------------
2
x = 2 + 4 or 2 -4
------- ------
2 2
x = 6/2 or -2/2
x = 3 or x = -1
Answer:
81x^4
Step-by-step explanation:
With exponents, whatever is in the parentheses is multiplied by <u>itself</u> however many times the exponent says.
In this case, you would be solving 3 x 3 x 3 x 3 and (x)^4.
3^4 = 81 with x^4 gives you:
81x^4
Hope this helps you :)